Inﬂuences of Ivabradine treatment on serum levels of cardiac biomarkers sST2, GDF-15, suPAR and H-FABP in patients with chronic heart failure - JIRAK Peter; FEJZIC Dzeneta; PAAR Vera; WERNLY Bernhard; PISTULLI Rudin; ROHM Ilonka; JUNG Christian; HOPPE Uta C; SCHULZE P Christian; LICHTENAUER Michael; YILMAZ Atilla; KRETZSCHMAR Daniel (Acta Pharmacologica Sinica, 2018)
Chronic heart failure (CHF) represents a major cause of hospitalization and death. Recent evidence shows that novel biomarkers such as soluble suppression of tumorigenicity (sST2), growth-differentiation factor-15 (GDF-15), soluble urokinase plasminogen activator receptor (suPAR) and heart-type fatty acid binding protein (H-FABP) are correlated with inflammatory and ischemic responses in CHF patients. In this study we examined the effects of Ivabradine that inhibited the hyperpolarization-activated cyclic nucleotide-gated channel (HCN channel, also called funny current If), thereby leading to selective heart rate reduction and improved myocardial oxygen supply on the cardiac biomarkers sST2, GDF-15, suPAR and H-FABP in 50 CHF patients at the University Hospital of Jena. Patients were divided into three groups based on the etiology of CHF: dilated cardiomyopathy (DCM, n=20), ischemic cardiomyopathy (ICM, n=20) and hypertensive cardiomyopathy (HCM, n=10). The patients were administered Ivabradine (5 mg, bid for 3 months, and 7.5 mg bid for further 3 months). Analyses of cardiovascular biomarkers were performed at baseline as well as at 3- and 6-month follow-ups. At 6-month follow-up, GDF-15 levels were significantly reduced compared to baseline levels (P=0.0215), indicating a reduction in the progress of cardiac remodeling. H-FABP concentration was significantly lower in DCM patients compared to ICM (1.89 vs 3.24 µg/mL) and HCM patients (1.89 vs 3.80 µg/mL), and decreased over the 6-month follow-up (P=0.0151). suPAR median levels remained elevated, implying major ongoing inflammatory processes. As shown by significant decreases in GDF-15 and H-FABP levels, a reduction in ventricular remodeling and sub-clinical ischemia could be assumed. However, markers of hemodynamic stress (sST2) and inflammation (suPAR) showed no change or progression after 6 months of Ivabradine treatment in CHF patients. Further studies are necessary to validate the clinical applicability of these novel cardiovascular biomarkers.